Molecule characterization of chemosensory and metabolism-related genes in the proboscis of Athetis lepigone - Tian, Cai-Hong; Liu, Xiao-Guang; Xu, Cun-Yi; Huang, Jian-Rong; Fu, Jun-Feng; Wang, Gen-Song; Zhang, Jun-Yi; Li, Guo-Ping; Yin, Xin-Ming; Feng, Hong-Qiang (Frontiers in Physiology, 2023)
The majority of moths primarily consume nectar or pollen from host plant flowers using an elongated proboscis, a trait commonly exploited for population monitoring and pest control. The moth species Athetis lepigone (Möschler) (Lepidoptera: Noctuidae), which has recently been identified as a pest of summer maize (Zea mays L.) in China, has demonstrated a rapid proliferation with in the Huang-Huai-Hai Plain region since its initial discovery in Hebei Province in 2005. It has become a prevalent pest of corn crops, and its ability to adapt quickly to its surroundings is currently being investigated. One of the key characteristics of its siphoning mouthparts is not only the feeding apparatus itself but also the chemosensory organs that enable the detection of chemical signals from the surrounding environment. However, there is a lack of comprehensive research on the genes responsible for chemosensory and metabolic mechanisms in the proboscises of male and female A. lepigone adults. In this study, we utilized transcriptome analysis to identify a total of fifty chemosensory genes from six distinct families, including 19 odorant-binding proteins (OBPs), 22 chemosensory proteins (CSPs), one co-receptor (Orco), six odorant receptors (ORs), four ionotropic receptors (IRs), and two sensory neuron membrane proteins (SNMPs) in the proboscis. Notably, seven OBPs, two CSPs, and one OR were discovered for the first time. Additionally, fourteen genes related to metabolism, including cytochrome P450 (CYPs) and carboxylesterases (CXEs), were also identified. Furthermore, a qualitative analysis was conducted on the relative transcript levels of eight related 删除了: Most moths feed on nectar or pollen from the flowers of 36 host plants via a long-extended proboscis. This characteristic is